Family 34 glycosyltransferase (GT34) genes and proteins in Pinus radiata (radiata pine) and Pinus taeda (loblolly pine). (26th March 2014) - Ade, Carsten P.; Bemm, Felix; Dickson, James M.J.; Walter, Christian; Harris, Philip J.
Summary Using a functional genomics approach, four candidate genes (PtGT34A, PtGT34B, PtGT34C and PtGT34D) were identified in Pinus taeda. These genes encode CAZy family GT34 glycosyltransferases that are involved in the synthesis of cell‐wall xyloglucans and heteromannans. The full‐length coding sequences of three orthologs (PrGT34A, B and C) were isolated from a xylem‐specific cDNA library from the closely related Pinus radiata. PrGT34B is the ortholog of XXT1 and XXT2, the two main xyloglucan (1→6)‐α‐xylosyltransferases in Arabidopsis thaliana. PrGT34C is the ortholog of XXT5 in A. thaliana, which is also involved in the xylosylation of xyloglucans. PrGT34A is an ortholog of a galactosyltransferase from fenugreek (Trigonella foenum‐graecum) that is involved in galactomannan synthesis. Truncated coding sequences of the genes were cloned into plasmid vectors and expressed in a Sf9 insect cell‐culture system. The heterologous proteins were purified, and in vitro assays showed that, when incubated with UDP‐xylose and cellotetraose, cellopentaose or cellohexaose, PrGT34B showed xylosyltransferase activity, and, when incubated with UDP‐galactose and the same cello‐oligosaccharides, PrGT34B showed some galactosyltransferase activity. The ratio of xylosyltransferase to galactosyltransferase activity was 434:1. Hydrolysis of the galactosyltransferase reaction products using galactosidases showed the linkages formed were α‐linkages. Analysis of the products of PrGT34B by MALDI‐TOF MS showed that up to three xylosyl residues were transferred from UDP‐xylose to cellohexaose. The heterologous proteins PrGT34A and PrGT34C showed no detectable enzymatic activity.